2021
DOI: 10.1093/gbe/evab222
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Mitochondrial Genomes in Gryllidea (Insecta: Orthoptera): Implications for Adaptive Evolution in Ant-Loving Crickets

Abstract: Species of infraorder Gryllidea, or crickets, are useful invertebrate models for studying developmental biology and neuroscience. They have also attracted attention as alternative protein sources for human food and animal feed. Mitochondrial genomic information on related invertebrates, such as katydids, and locusts, has recently become available in attempt to clarify the controversial classification schemes, although robust phylogenetic relationships with emphasis on crickets remain elusive. Here, we report n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 27 publications
7
24
0
Order By: Relevance
“…A similar situation was observed between P12 and P12R trees, reflecting that the exclusion of the rRNA genes can improve branch supports of phylogenetic trees. The monophyly of the infraorder Gryllidea was well supported by all datasets with high nodal supports (PPs = 1; BSs = 100), and consistent with the results proposed by Chintauan-Marquier et al [ 17 ], Zhou et al [ 48 ], Chang et al [ 10 ], Song et al [ 8 ] and Sanno et al [ 18 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A similar situation was observed between P12 and P12R trees, reflecting that the exclusion of the rRNA genes can improve branch supports of phylogenetic trees. The monophyly of the infraorder Gryllidea was well supported by all datasets with high nodal supports (PPs = 1; BSs = 100), and consistent with the results proposed by Chintauan-Marquier et al [ 17 ], Zhou et al [ 48 ], Chang et al [ 10 ], Song et al [ 8 ] and Sanno et al [ 18 ].…”
Section: Resultssupporting
confidence: 89%
“…Most of them are complete triplet bases TAA/TAG, and others are incomplete T/TA immediately followed by or partially overlapped with a tRNA gene. Incomplete stop codons are fairly common in the orthopteran mitogenomes and can be converted into a potential stop codon via polyadenylation to TAA [ 18 , 39 , 40 , 55 ]. The results of RSCU analyses show that the PCGs exhibit strong biases toward the nucleotides A and U in the codon usage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Recent studies using the mitochondrial genome and a combination of nuclear and mitochondrial genes have shown that Grylloidea and Gryllotalpoidea are monophyletic sister groups (Song et al 2015;Chintauan-Marquier et al 2016;Zhou et al 2017;Yang et al 2021;Sanno et al 2021). However, other studies or approaches have either not confirmed this relationship or have produced conflicting phylogenetic relationships (Song et al 2020;Sanno et al 2021).…”
Section: Gryllideamentioning
confidence: 99%
“…Recent studies using the mitochondrial genome and a combination of nuclear and mitochondrial genes have shown that Grylloidea and Gryllotalpoidea are monophyletic sister groups (Song et al 2015;Chintauan-Marquier et al 2016;Zhou et al 2017;Yang et al 2021;Sanno et al 2021). However, other studies or approaches have either not confirmed this relationship or have produced conflicting phylogenetic relationships (Song et al 2020;Sanno et al 2021). To fully understand the phylogenetic relationship between Grylloidea and Gryllotalpoidea, we need genome sequences of a wide range of species included in this infraorder, which enable usage of single-copy gene sequences for building Fig.…”
Section: Gryllideamentioning
confidence: 99%